Controlled Growth of CdS Nanostep Structured Arrays to Improve Photoelectrochemical Performance - Jiang, Jiangang; Wang, He; An, Hongchang; Du, Guangyuan (Frontiers in Chemistry, 2020)
CdS nanostep-structured arrays were grown on F-doped tin oxide-coated glasses using a two-step hydrothermal method. The CdS arrays consisted of a straight rod acting as backbone and a nanostep-structured morphology on the surface. The morphology of the samples can be tuned by varying the reaction parameters. The phase purity, morphology, and structure of the CdS nanostep-structured arrays were characterized by X-ray diffraction and field emission scanning electron microscopy. The light and photoelectrochemical properties of the samples were estimated by a UV-Vis absorption spectrum and photoelectrochemical cells. The experimental results confirmed that the special nanostep structure is crucial for the remarkable enhancement of the photoelectrochemical performance. Compared with CdS rod arrays, the CdS nanostep-structured arrays showed increased absorption ability and dramatically improved photocurrent and energy conversion efficiency. This work may provide a new approach for improving the properties of photoelectrodes in the future.